TIPOLOGIZATION OF HIGHER EDUCATION INSTITUTIONS IN THE CONTEXT OF MANAGEMENT UPGRADING OF THE EDUCATIONAL INSTITUTIONS - S. Kuizheva; A. Babikova (Вестник университета)
Functioning of higher education institutions in modern conditions demands revision of the existing approaches for managing them in the direction of finding the mechanisms providing along with the improvement of educational process quality, their integration into world educational space. The typology of higher education institutions on the basis of university presentation in the form of the educational corporation, integrating different directions, possessing the multilevel structure uniting interests of various groups is offered. Referring the higher education institution to this or that type, taking into account inherent features, will allow to offer to a concrete higher education institution that vector of development, which will provide the transition to qualitatively new level and will allow to correlate the advanced educational technologies to fundamental knowledge and institutional conditions, to create the trajectory focused on break in a wide range of fundamental and applied sciences.